Change Characteristics and Correlation Analysis of Temperature and Rainfall in Recent 60 Years in Suzhou, Jiuquan - FENG Shiyuan; LI Qingguo; GUO Yang; ZHENG Shuai (Renmin Zhujiang)
In order to reveal the change trend and rule of temperature and rainfall in the Suzhou,Jiuquan, this paper analyzes the rainfall and temperature data of the study area from 1951 to 2018by the trend analysis,abrupt change test, R/S analysis and wavelet analysis method. The resultsshow that: The annual average temperature of the study area rises obviously, with the risingtendency rate of about 0.229 ℃/(10a), the abrupt change point of annual average temperature isaround 1997, and the temperature increase trend is more significant after 1999. Combined with R/Sanalysis, the Hurst index is 0.958, which indicates that the future temperature in Suzhou willcontinue to rise; The annual rainfall of the study area fluctuated sharply before 2000, andincreased after 2000, with the rising tendency trend of 2.96 mm/(10a). The abrupt change of annualrainfall occurred after 2005, and the oscillation changes of annual rainfall within the abruptchange interval were obvious. Combined with R/S analysis, the Hurst index is 0.5578, whichindicates that the rainfall will continue to rise in the future. The continuous wavelet indicatesthat the annual rainfall and temperature has periodicity,while the cross-wavelet and waveletcoherence spectrum indicate that there is the correlation and resonance cycle ina period of timebetween the annual rainfall and temperature.